Pengembangan Media Pembelajaran Interaktif Berbasis Macromedia Flash 8 pada Materi Sistem Tata Surya di Madrasah Ibtidaiyah - Darmayanti, Syarifah Dewi; Mislan; Wiratama, Arif (Kartika: Jurnal Studi Keislaman, 2026)
This study aims to develop an interactive learning media based on Macromedia Flash 8 for the solar system material in Madrasah Ibtidaiyah and to analyze its validity, practicality, and effectiveness. The study employed a Research and Development (R&D) method using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. Data were collected through observation, interviews, questionnaires, and learning achievement tests. The research subjects included material experts, language experts, media experts, teachers, and sixth-grade students of Madrasah Ibtidaiyah. The data were analyzed using feasibility percentages and N-Gain calculations. The results showed that the developed learning media achieved a very high level of validity, with material expert validation reaching 92%, language expert validation 90%, and media expert validation 100%. In terms of practicality, the teacher response reached 93%, while student responses in small-group and large-group trials reached 93% and 91%, respectively, categorized as very good. Furthermore, the effectiveness test indicated an improvement in students’ learning outcomes, with the average pretest score increasing from 74 to 90 in the posttest, and an N-Gain score of 0.62 categorized as moderate. The Macromedia Flash 8-based interactive learning media can help visualize abstract concepts in the solar system material and improve students’ engagement and conceptual understanding in IPAS learning